PERANCANGAN STRATEGI KOMUNIKASI DIGITAL DAN PROMOSI UNTUK MENINGKATKAN PENJUALAN BRAND KAOS IKUZO - Widjaja, Felicia Emily; Sidik, Reviana Nathalia (Kartala, 2024)
Anime has been commonly known widely across the globe with its loyal community consuming varies of anime contents and products, including fashion anime. One of Bandung local clothing brand, named Ikuzo also highlighted anime characters as its excellence t-shirt design. Started in June 2021, Ikuzo presents its unique design through various anime characters and meaningful messages specially designed by Ikuzo. As a newborn local brand, Ikuzo still need to commucicate its core values and products to its local commnunity in its hometown Bandung, since its most customers actually came from cities outside Bandung. Data collection was conducted using literature study, direct interview with owner and distributed questionnaire to 148 repondents in Bandung, age 16-25 years old to study their motivations, tastes and needs toward anime clothing. SWOT analysis was used to mapped Ikuzo’s potential in clothing industry which then being translated to visual studies and communication strategies for designing the digital marketing communication promotion design contents on various digital platforms. As a result, Ikuzo could gain higher brand awareness, reached wider market in Bandung which led to the increasing total sales of Ikuzo.